Relevance of Civil Engineering Vocational Education Graduates’ Competence with Productive Skill Teacher Competency - Mayasari, Retno; Samsudi, Samsudi; Qudus, Nur (Journal of Vocational and Career Education, 2018)
This study aims to analyze the relevance of the competence of Civil Engineering vocational Education Department graduates with the competence of productive skill teachers in vocational schools. Competencies analyzed in this studywere pedagogic competence and professional competence. This study was descriptive quantitative then converted and summed up into qualitative form. The subjects of this study were 24 respondents from the alumni of Civil Engineering Vocational Education Department, UNNES class of 2008, 2009, 2010, and 2011. Data collection was conducted using questionnaires and documentation. The data were analyzed using descriptive percentage. The result of the studywas the relevance level of pedagogic competence and professional competence of the graduatesof the Civil Engineering Vocational Education Department that has become productive skill teachers. The relevance percentage of the curriculum of Civil Engineering Vocational Education Department with the curriculum of Civil EngineeringEducation program at the vocational schools was 84.88%. It showed that curriculum structure of the curriculum of Civil Engineering Vocational Education Departmenthad slight irrelevance withthat of Civil EngineeringEducation program.A curriculum structurewas not relevant. The relevance percentage of the pedagogic competence of the Civil Engineering Vocational Education Department with the curriculum of Civil EngineeringEducation program at the vocational schoolswas 86, 50%. This percentage meant that the curriculum at Civil Engineering Vocational Education Departmenthas not been all relevant to those demanded in the curriculum of Civil EngineeringEducation program at the vocational school. However, the pedagogic competence of Civil Engineering Vocational Education Department’graduates can be categorized as very relevant. The percentage of professional competence showed88.81%, which meant that for professional competence of Civil Engineering Vocational Education Department’ graduates can be categorized as very relevant.